The impact of red blood cell surface properties on the functioning of the vascular system - Neu, Bjoern Holger (2015)
The long-term goal of this study is to understand cellular factors affecting red blood cell (RBC) aggregation and RBC adhesion to endothelial cells as well as the significance of such factors in diseases associated with vascular complications. Past works dealing with abnormal RBC aggregation and adhesion have mostly focused on plasma factors and on the expression of cell surface receptors. However, also due to our recent work in the field of RBC aggregation it became evident that abnormal RBC interactions are at least partly due to changes of non-specific forces caused by abnormal cell-surface properties. This project investigated RBC aggregation and adhesion in plasma like media in order to achieve a clearer understanding of cellular properties affecting RBC interactions and on defining cellular factors critical for such interactions.